Flutter and divergence of sweptback and sweptforward wings - Babister, A. W. (College of Aeronautics, Cranfield, 1950)
In this note, the equations of the flexural-torsional flutter of a swept wing are established, assuming the wing to be semi-rigid and fixed at the root. The general effect of sweepback, wing stiffness and position of the inertia axis are determined. The critical speeds for flutter and for wing divergence are determined (i) for incompressible flow (ii) for compressible flow, assuming a modified Glauert correction. The critical flutter speed is in general higher for a sweptback wing having the same wing stiffness as the upswept wing; foe a swept forward wing, divergence will occur before flutter.